Investing in Gender-Equal Sustainable Development - Isha Ray (United Nations)
This work develops an agenda for investing in sustainable development, with particular emphasis on local priorities, poverty alleviation and gender equality. Sustainable development can take many different pathways, even within the dominant ‘three-pillar’ paradigm (economy-environment-society) of sustainability. The author draws on the vast literature on access to basic services for the poor to argue that universal and gender-equal access cannot be guaranteed primarily by voluntary mechanisms (i.e., through market forces or through the non-governmental sector). Universal access needs a renewal of the civic contract between the state and its citizens. As we begin the post-2015 era, promoting public action towards gender-equal development should become a priority for the sustainable development agenda.